The Role of Firm Size in Strengthening the Relationship between Profitability, Capital Structure, and Affiliated Transactions on Tax Advoidance - Nugraha, Indra; Rachmat, Radhi Abdul Halim (Magister Akuntansi Universitas Pancasila, 2024)
Purpose: The purpose of this study is to determine the effect of profitability, capital structure, and affiliate transactions on tax avoidance practices, with firm size as a moderating variable. Methodology: The method used in this study is quantitative research. Hypothesis testing in this study uses Moderated Regression Analysis (MRA) and classical assumption testing uses the eviews 13 application. Finding: Profitability and affiliated transactions have a negative effect on tax avoidance behavior and capital structure has a positive effect on tax avoidance behavior, while firm size as a moderation cannot strengthen profitability, capital structure and affiliated transactions on tax avoidance behavior. Implication: Providing insights for tax policy makers and regulators on factors that influence tax avoidance in companies and are important for company management, providing important information on how financial and operational decisions can affect tax liabilities, and tax authorities can develop more effective strategies to improve tax compliance. Originality: The originality of this study lies in its specific geographical focus, innovative methodological approach, comprehensive integration of variables, and potential broad practical implications. This study contributes significantly to the academic and practical literature in the field of corporate tax and financial management, especially in the context of a developing country like Indonesia.